An apparent “vital effect” of calcification rate on the Sr/Ca temperature proxy in the reef coral Montipora capitata - Ilsa B. Kuffner; Paul L. Jokiel; Ku'ulei S. Rodgers; Andreas J. Andersson; Fred T. Mackenzie (Geochemistry, Geophysics, Geosystems, 2012)
Measuring the strontium to calcium ratio in coral skeletons reveals information on seawater temperatures during skeletal deposition, but studies have shown additional variables may affect the ratio. Here we measured Sr/Ca in the reef coral Montipora capitata grown in six mesocosms continuously supplied with seawater from the adjacent reef flat. Three mesocosms were ambient controls, and three had seawater chemistry simulating “ocean acidification” (OA). We found that Sr/Ca was not affected by the OA treatment and neither was coral calcification for these small colonies (larger colonies did show an OA effect). The lack of OA effects allowed us to test the hypothesis that coral growth rate can affect Sr/Ca using the natural range in calcification rates of the corals grown at the same temperature. We found that Sr/Ca was inversely related to calcification rate (Sr/Ca = 9.385 − 0.0040 (calcification rate)). Using a previously published calibration curve for this species, a 22 mg d−1 colony−1increase in calcification rate introduced a 1°C warmer temperature estimate, with the 27 corals reporting “temperatures” ranging from 24.9 to 28.9°C, with mean 26.6 ± 0.9°C standard deviation. Our results lend support to hypotheses invoking kinetic processes and growth rate to explain vital effects on Sr/Ca. However, uncertainty in the slope of the regression of Sr/Ca on calcification and a low R‐squared value lead us to conclude that Sr/Ca could still be a useful proxy in this species given sufficient replication or by including growth rate in the calibration.